Circadian CLOCK gene polymorphisms in relation to sleep patterns and obesity in African Americans: findings from the Jackson heart study - Riestra, Pia (BMC Genet, 2017)
BACKGROUND: Circadian rhythms regulate key biological processes and the dysregulation of the intrinsic clock mechanism affects sleep patterns and obesity onset. The CLOCK (circadian locomotor output cycles protein kaput) gene encodes a core transcription factor of the molecular circadian clock influencing diverse metabolic pathways, including glucose and lipid homeostasis. The primary objective of this study was to evaluate the associations between CLOCK single nucleotide polymorphisms (SNPs) and body mass index (BMI). We also evaluated the association of SNPs with BMI related factors such as sleep duration and quality, adiponectin and leptin, in 2962 participants (1116 men and 1810 women) from the Jackson Heart Study. Genotype data for the selected 23 CLOCK gene SNPS was obtained by imputation with IMPUTE2 software and reference phase data from the 1000 genome project. Genetic analyses were conducted with PLINK RESULTS: We found a significant association between the CLOCK SNP rs2070062 and sleep duration, participants carriers of the T allele showed significantly shorter sleep duration compared to non-carriers after the adjustment for individual proportions of European ancestry (PEA), socio economic status (SES), body mass index (BMI), alcohol consumption and smoking status that reach the significance threshold after multiple testing correction. In addition, we found nominal associations of the CLOCK SNP rs6853192 with longer sleep duration and the rs6820823, rs3792603 and rs11726609 with BMI. However, these associations did not reach the significance threshold after correction for multiple testing. CONCLUSIONS: In this work, CLOCK gene variants were associated with sleep duration and BMI suggesting that the effects of these polymorphisms on circadian rhythmicity may affect sleep duration and body weight regulation in Africans Americans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12863-017-0522-6) contains supplementary material, which is available to authorized users.